ANALISIS PERAN GURU SEBAGAI KOMUNIKATOR DALAM MENINGKATKAN MOTIVASI BELAJAR PAK SISWA KELAS VIII - Hotlin Simamora (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2019)
Abstract -  This study aims to analyze how the role of the teacher as a communicator in increasing motivation to learn PAK class VIII SMP Negeri 1 Pangaribuan Learning Year 2018/2019. With the hypothesis the research is: the role of the teacher as a communicator in increasing students' PAK learning motivation 70% than expected. This study uses quantitative descriptive methods, with a population of 217 people and a sample of 34 people. Data was collected with a closed questionnaire instrument. The questionnaire trial was conducted on 32 students in Pangaribuan Middle School 1 who were not research respondents. Test the validity of the instrument using the Pearson Product Moment Correlation Coefficient formula obtained rcount rtable (0.351 to 0.689 0.349) so that the instrument is valid. Meanwhile there are 3 invalid items between the values of 0.134 to 0.233. And the reliability test of the instrument with the Cronbach Alpha formula obtained r11 = 0.903 is in the high category, so the instrument is reliable. The results of data analysis showed that the value of the formula t as testing criteria then obtained tcount t table of 6.029 1.697 means that the teacher acts as a communicator in increasing motivation to learn PAK class VIII Pangaribuan Middle School Learning Year 2018-2019 70% than expected. Thus the research hypothesis is accepted.Keywords: Teachers as Communicators, PAK Learning Motivation